2014
DOI: 10.1101/cshperspect.a018358
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and Autophagy: Exploitation or Cooperation?

Abstract: Autophagy is a lysosome-mediated degradative system that is a highly conserved pathway present in all eukaryotes. In all cells, double-membrane autophagosomes form and engulf cytoplasmic components, delivering them to the lysosome for degradation. Autophagy is essential for cell health and can be activated to function as a recycling pathway in the absence of nutrients or as a quality-control pathway to eliminate damaged organelles or even to eliminate invading pathogens. Autophagy was first identified as a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
168
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(170 citation statements)
references
References 101 publications
2
168
0
Order By: Relevance
“…PI(3)P also plays a direct role in endosome mobility by recruiting the kinesin-3, KIF16B, which contains a PI(3)P-binding PX domain . Similarly, the plus end-directed transport of autophagic vesicles, which fuse with late endocytic elements, is promoted by the PI(3)P effector FYCO1 (FYVE and coiled-coil domaincontaining protein 1) (Pankiv et al 2010), in line with the fact that PI(3)P is required for autophagosome biogenesis via recruitment of PI(3)P effectors (Simonsen et al 2004;Filimonenko et al 2010;Noda et al 2010;Tooze et al 2013).…”
Section: Lipids As Organizing Principles Of Peripheral Membrane Proteinsmentioning
confidence: 66%
See 1 more Smart Citation
“…PI(3)P also plays a direct role in endosome mobility by recruiting the kinesin-3, KIF16B, which contains a PI(3)P-binding PX domain . Similarly, the plus end-directed transport of autophagic vesicles, which fuse with late endocytic elements, is promoted by the PI(3)P effector FYCO1 (FYVE and coiled-coil domaincontaining protein 1) (Pankiv et al 2010), in line with the fact that PI(3)P is required for autophagosome biogenesis via recruitment of PI(3)P effectors (Simonsen et al 2004;Filimonenko et al 2010;Noda et al 2010;Tooze et al 2013).…”
Section: Lipids As Organizing Principles Of Peripheral Membrane Proteinsmentioning
confidence: 66%
“…However, we still know relatively little about their exact functions. In yeast PI(3,5)P 2 -binding PROPPIN proteins, such as Atg18 and Atg21, have been implicated in autophagosome maturation and vacuole homeostasis (Mayinger 2012;Tooze et al 2013). Further roles of PI(3,5)P 2 in animal cells seem to be the activation of mucolipin transient receptor potential ion channel (Dong et al 2010), regulation of autophagy in the nervous system (Ferguson et al 2010), and cardiac contractility via activation of the ryanodine receptor (Touchberry et al 2010).…”
Section: Endosomal Lipidsmentioning
confidence: 99%
“…The endosomal RAB proteins RAB4 (Talaber et al, 2014), RAB5 (Ravikumar et al, 2008), RAB7 (Gutierrez et al, 2004;Jäger et al, 2004;Pankiv et al, 2010;Tabata et al, 2010) and RAB11 (Fader et al, 2008;Knaevelsrud et al, 2013;Longatti et al, 2012;Puri et al, 2013) have all been shown to play a role in autophagy. However, as endosomes have a dual role in autophagy, because they fuse with autophagosomes after their closure and, at the same time, provide membrane input to the forming phagophore, it is difficult to interpret the function of the different endosomal RAB proteins in autophagy (for recent reviews, see Szatmári and Sass, 2014;Tooze et al, 2014).…”
Section: Tethering and Fusion Of Incoming Phagophore Membranesmentioning
confidence: 99%
“…Recent work summarized by Settembre and Ballabio (2014) has provided insights into the transcriptional regulation of lysosome biogenesis, autophagy, and clearance. The article by Tooze et al (2014) describes recent progress in autophagy or "self-eating," a cellular repair mechanism very important for cell homeostasis, defense mechanisms, and the prevention of a number of human diseases. Not surprisingly, given its evolutionary importance, as suggested by de Duve, many of the proteins that drive endocytosis are highly conserved and can be traced to the earliest eukaryotic ancestors; more recent additions to the endocytic machinery are likely indicative of specialization and increased regulation of the endocytic pathways during evolution (as discussed in the article by Wideman et al 2014).…”
Section: Overview Of Articlesmentioning
confidence: 99%